Soil and Water Conservation Measures Improve Soil Microbial Activity and Carbon Sequestration: A Study on High Density Cashew in West Coast Region of India - Bappa Das, Dayesh Murgaokar, Ashwini S. Desai, Shaiesh Morajkar and Rahul M. Kulkarni, G.R. Mahajan*, Sujeet Desai, S. Manivannan, B.L. Manjunath (Journal of the Indian Society of Soil Science, 2022)
A 13-years study was conducted from 2001 to 2013 to assess the effect of soil and water conservation (SWC) measures on soil microbial activity and carbon sequestration under high density (4 m Ã— 4 m) cashew nut on 19% sloping land in the west coast region of India. Five SWC measures namely, continuous contour trenches + vegetative barrier (CCT+VB), staggered contour trenches + vegetative barrier (SCT+VB), crescent shape trench + vegetative barrier (CST+VB), vegetative barrier (VB), and control with no SWC measures were evaluated. The CCT+VB showed the best performance with significantly higher soil organic carbon (SOC) (1.41 to 2.02%) and SOC stock (SOCS) (44.9-57.8 Mg C ha-1) compared to control up to a depth of 0-0.9 m. The same treatment had significantly higher SOC sequestration rate (SOCSR) of 1.5 Mg C ha-1 yr-1 with significantly (p